2020
DOI: 10.21203/rs.3.rs-114758/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug Repurposing for COVID-19 using Graph Neural Network with Genetic, Mechanistic, and Epidemiological Validation

Abstract: Amid the pandemic of 2019 novel coronavirus disease (COVID-19) infected by SARS-CoV-2, a vast amount of drug research for prevention and treatment has been quickly conducted, but these efforts have been unsuccessful thus far. Our objective is to prioritize repurposable drugs using a drug repurposing pipeline that systematically integrates multiple SARS-CoV-2 and drug interactions, deep graph neural networks, and in-vitro/population-based validations. We first collected all the available drugs (n= 3,635) involv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 79 publications
0
25
0
Order By: Relevance
“…Among the 231 articles (PubMed and Google Scholar), 91 were retained [ 3 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Update (16 June 2021) On Studies With Fiasmas In the Sars-cov-2 Infectionmentioning
confidence: 99%
“…Among the 231 articles (PubMed and Google Scholar), 91 were retained [ 3 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Update (16 June 2021) On Studies With Fiasmas In the Sars-cov-2 Infectionmentioning
confidence: 99%
“…The results showed that 380 KDTs have a direct relation with circuits of the COVID-19. In [ 174 ], the authors used a deep graph neural network to extract the candidate drug representation according to biological interactions. They demonstrated that the interactions between DNN and extensive interaction could facilitate the identification of candidate drugs.…”
Section: The Study Taxonomymentioning
confidence: 99%
“…In the first set of studies, (11,12,(14)(15)(16)(17)(18) the antiviral activity of FIASMAs against the SARS-CoV and MERS-CoV viruses was explored. In the second set of studies, different drugs were tested against the SARS-CoV-2 using in silico (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and in vitro studies. (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) These are listed in Table 1.…”
Section: Fiasma's and Coronavirusesmentioning
confidence: 99%